Modelling the lateral pedestrian force on rigid and moving floors by a self-sustained oscillator - Trovato, Andrea; Olivito, Renato S.; Bruno, Domenico; Argoul, Pierre (My University, 2009)
For the serviceability analysis of civil engineering structures under human induced vibrations, a correct modelling of the pedestrian-structure interaction is needed. The proposed approach consists in thinking the human body as a Single Degree of Freedom oscillator: the force transmitted to the floor is the restoring force of this oscillator [1, 2]. In rigid floor conditions, such an oscillator must be able to reproduce two experimentally observed phenomena: (i) the time-history of lateral force can be approximated by a periodic signal with a “natural” frequency related with the single pedestrian characteristics; (ii) the motion of a pedestrian is self-sustained, in the sense that the pedestrian produces by itself the energy needed to walk. Accounting for these aspects, a modified Van der Pol (MVdP) oscillator is proposed here to represent the lateral pedestrian force. The suitable form of its nonlinear restoring force is inferred from experimental data concerning a sample of twelve pedestrians. The experimental and model lateral forces show an excellent agreement. For a laterally moving floor, the MVdP oscillator representing a pedestrian becomes non-autonomous. It is well-known that self-sustained oscillators in the non-autonomous regime are characterized by the so-called entrainment phenomenon. It means that under certain conditions, the vibration frequency switches from the ”natural” value to that of the external force: the response frequency is entrained by the excitation frequency. According to the physical interpretation considered here, the entrainment corresponds to the situation where the pedestrian changes its natural walking frequency and synchronizes with the floor oscillation frequency. The steady response of the MVdP oscillator subjected to a harmonic excitation is discussed in terms of non-dimensional amplitude response curves, obtained using the harmonic balance method truncated at the first harmonic. The model predictions are compared with some experimental results concerning pedestrians available in the literature and a good agreement is obtained. These topics are detailed in this thesis and also in the companion papers [3, 4] and in the report [5].
Dottorato di Ricerca in Ingegneria dei Materiali e delle Strutture, Ciclo XXI, 2009
Keywords: Ingegneria; Strutture; Materiali stradali; Meccanica Laminati; Oscillatori